Ski-ba-bop-ba-dop-bop - Scatman John, (John Paul Larkin); Catania, Antonio Nunzio; Kays, Ingo; BMG UFA.; EMI Music (Germany : BMG UFA, 1994)
Contains an electro-hop single taken from the album Scatman's World.
CD 1 : Scatman (Basic-Radio) / (3:30) -- Scatman (Jazz-Level) / (3:41) -- Scatman (Second-Level) / (5:40) -- Scatman (Third-Level) / (5:46) -- Scatman (Game-Over-Jazz) / (5:03).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Techno music